Палеолитические стоянки Карабай I и Карабай II: предварительные результаты исследований - Евтушенко, А.И. (Археологический альманах, 2009)
Karabai I and Karabai II are recently discovered Middle Paleolithic localities situated in northern part of the Internal Range of the Crimean Mountains at 2 km south to Mironovka village (Fig. 1). The sites are located in Karabai-Kuba Ravine which is one of several east-trending drainages cut the edge of rocky Sary-Kaya Plateau risen above left bank of the valley of Bijuk-Karasu River.